Integração do passkeys em Provedores de Identidade Shibboleth - Rosa, Andrey Adriano da; Mello, Emerson Ribeiro de (Companion Proceedings of the Brazilian Symposium on Cybersecurity (SBSeg); 2023: Companion Proceedings of the 23rd Brazilian Symposium on Information and Computational Systems SecurityDO - 10.5753/sbseg_estendido.2023.235836, 2023)
User authentication based on passwords is susceptible to various attacks and imposes a significant cognitive load on users. Multi-factor authentication seeks to minimize the effectiveness of certain remote attacks, but it often penalizes usability. Passkeys, a term coined based on recent standards from the FIDO Alliance and W3C, emerge as a robust alternative with a focus on usability for remote user authentication on the web. This work presents a solution for integrating passkeys into Shibboleth Identity Providers, enabling their use both as a second factor and as the first authentication factor.